A chiral GC-MS method for analysis of secondary amino acids after heptafluorobutyl chloroformate & methylamine derivatization - Opekar, Stanislav; Zahradníčková, Helena; Vodrážka, Petr; Řimnáčová, Lucie; Šimek, Petr; Moos, Martin (Amino acids, 2021)
L-amino acids (L-AAs) play different important roles in the physiology of all living organisms. Their chiral counterparts, D-amino acids (D-AAs) are increasingly being recognized as essential molecules in many biological systems. Secondary amino acids with cyclic structures, such as prolines, exhibit conformational rigidity and thus unique properties in the structural and protein folding. Despite their widespread occurrence, much less attention was paid to their chiral analysis, particularly when the minor, typically D-enantiomer, is present in low amounts in a complex biological matrix. In this paper, a cost-effective, chiral GC-MS method is described for capillary Chirasil-L-Val separation of nine cyclic secondary amino acid enantiomers with four-, five-, and six-membered rings, involving azetidine-2-carboxylic acid, pipecolic acid, nipecotic acid, proline, isomeric cis/trans 3-hydroxy, 4-hydroxyproline, and cis/trans-5-hydroxy-L-pipecolic acid in the excess of its enantiomeric antipode. The sample preparation involves in-situ derivatization with heptafluorobutyl chloroformate, simultaneous liquid-liquid micro-extraction into isooctane followed by amidation of the arising low-polar derivatives with methylamine, an evaporation step, re-dissolution, and final GC-MS analysis. The developed method was used for analyses of human biofluids, biologically active peptides containing chiral proline constituents, and collagen.
Keywords: Reproducibility of Results; Imino Acids; reprodukovatelnost výsledků; Stereoisomerism; kalibrace; Methylamines; fluorokarbony; methylaminy; iminokyseliny; Enantiomeric separation; GC–MS; Fluorocarbons; stereoizomerie; Secondary amino acids; Calibration; Humans; Methyl amide derivatives; plynová chromatografie s hmotnostně spektrometrickou detekcí; formiáty; Imino acids; Formates; Heptafluorobutyl chloroformate; Gas Chromatography-Mass Spectrometry; lidé